A study of subject-verb agreement: from novice writers to expert writers - Nayan, Surina; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Students in higher learning institutions need to write lots of reports based on the projects done. Since they are at the tertiary level of education, they are required to use English in their reports. This is to ensure that they are able to function well in English later at the workplace. Writing requires students to apply rules regarding sentence structures, grammar and also its mechanic that refers to punctuation and capitalization. However, many of the students have problems in applying these rules in their writing even though they have been learning English for about 12 years in school. This is a case study on BEL 311, semester 3 students at one local higher learning institution that comprises ‘Bumiputra’ (a Malay term widely used in Malaysia, embracing ethnic Malays, Javanese, Bugis, Minang and other indigenous ethnic groups such as the Orang Asli in Peninsular Malaysia and the tribal peoples in Sabah and Sarawak) students regarding their problems with subject-verb agreement in their writing. These students are required to write a term paper that worths 30% out of their 100% total score. They are taking their BEL 311, English for Academic Purposes –an undergraduate diploma course. The researcher gathered information for this study through her observation, interview and written assignment given to students. The findings from the study are of significant important since this will help the lecturers to further enhance their teaching methods and find ways to help students improve their writing and avoid making errors in subject-verb agreement as possible.